A 5.1% efficient kesterite Cu2ZnSnS4 (CZTS) thin film solar cell prepared using modified sulfurization process. Issue 6 (7th April 2015) - Gang, Myeng G.; Gurav, Kishor V.; Shin, Seung W.; Hong, Chang W.; Min, Jung H.; Suryawanshi, Mahesh P.; Vanalakar, Sharad A.; Lee, Dong S.; Kim, Jin H.; Tsuboi, Nozomu; Wakita, Kazuki; Yamada, Akira; et al.
Abstract Cu2ZnSnS4 (CZTS) absorber thin films are prepared by sulfurization of sputtered Cu/Sn/Zn (CZT) stacked metallic precursor. The modified sulfurization process is adapted to prepare photovoltaic quality CZTS films. Specifically, sputtered CZT precursor films are sulfurized in sulfur powder contained graphite box using rapid thermal processing furnace at 580 °C for 10 min, in N2(95%) + H2S (5%) atmosphere. The Cu‐poor CZTS films with various Cu/(Zn+Sn) ratio are prepared by varying Cu layer deposition time. The effect of Cu/(Zn+Sn) ratio on the properties of CZTS films is investigated. The CZTS thin film solar cells with Cu/(Zn+Sn)=0.76 shows best conversion efficiency of 5.1% (Voc: 573 mV, Jsc: 18.38 mA/cm2, FF: 0.48%, and active area: 0.31 cm2). (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)